Within and between person effects of learning agility: a longitudinal examination of how learning agility impacts future career success - Laxson, Erin N., author; Kraiger, Kurt, advisor; Albert, Lumina, committee member; Dik, Bryan, committee member; Gibbons, Alyssa, committee member (Colorado State University. Libraries, 2018)
The business environment is highly complex and constantly evolving. Previous research on learning agility has demonstrated support for its use in identifying high potential leaders who can adapt effectively to the evolving business environment. The purpose of this study was to provide further evidence of the construct validity of learning agility and applicability in assessing leadership potential. Learning agility was examined within a broader nomological network of related constructs—a framework developed by DeRue, Ashford, & Myers (2012). It was hypothesized that personality would predict learning agility and learning agility would predict performance and learning over time. The results demonstrate partial support for these hypotheses. Several personality variables (e.g., Openness to Experience) were significantly related to learning agility. Further, learning agility was found to predict performance and learning, but not the rate at which these factors changed over time.
Keywords: learning agility; personality; performance; learning